REKRUTMEN POLITIK PARTAI DEMOKRAT TAHUN 2013 DI KABUPATEN KUANTAN SINGINGI - Biyanca Duta Pratama; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study wanted to know why the cadres of other political parties chose to move to the Democratic Party and also want to know how the contribution generated by the new members recruited Branch Council of the Democratic Party Singingi Kuantan District. The background of this study is as a consequence of the Parliamentary system where the threshold for political parties that do not mecapai threshold numbers can no longer follow the next general election but to join another political party if you want to follow the next general election. So that three cadres namely the Patriot Party, National Party Indonesia Marhaneisme, and Ulema National Awakening Party's seat in the House of Representatives District Kuantan Singingi and intend to advance in the general election of 2014 had to resign from the previous political party to move to the Democratic Party. This study used qualitative methods are implemented in the Democratic Party Branch Council Kuantan Singingi, data obtained either directly or indirectly, which is then analyzed using descriptive data analysis techniques.Based on the results of research in the field with the fact - the fact that it appears that this happened because of political recruitment peer relationships among members of the House of Representatives District Singingi Kuantan is the chairman of the Democratic Party with the three members who were recruited from the other party. Then the recruitment is done in order to fill vacancies for qualified cadres can be nominated at the 2014 general election in order to win the fight seats in the House of Representatives District Singingi Kuantan. This is due to the impact of the dualism of the internal leadership of the Democratic Party so that there is a cadre who came out as opposed to the legitimate leadership or management. Then the contribution of recruitment of new members nominated at the last general election in 2014 the Democratic Party is able to maintain the number of seats in the House of Representatives Regency Kuantan Singingi and also an increase in the acquisition of significant noise experienced by the Democratic Party which in 2009 only gained 8798 votes, while in 2014 were able to obtain 16 191 voice or sound 94% increase. Thus meaning that the Democratic Party political recruitment success, despite internal conflicts within the party.Keywords : Rekruitmen Politic, Democratic Party District Kuantan Singingi